Eğitimci Kimliğiyle Bedri Rahmi Eyüboğlu - Aldoğan, Semra (Sosyal Bilimler Enstitüsü, 2003)
1942-1975 yıllan arasında İstanbul Devlet Güzel Sanatlar Akademisi' nde atölye hocalığı yapan Bedri Rahmi Eyüboğlu'nun en önemli yönü her türlü görüşe çok açık olmasıdır ve atölyesinin en baskm yönü serbest ve özgür bir atölye olmasıdır. Öğrencilerine öncelikli olarak ressam olmanın ötesinde, sanatçı olmayı ve o sanatçı tavrı tüm yaşamları boyunca takınarak bunu yaşam tarzı ve hayat felsefesi haline getirmeyi öğretmiştir. Atölyesinde yetiştirdiği öğrencilerinin de büyük bir kısmı bu anlayışı benirnserniştir ve bu nedenle hala birçok öğrencisi yaşamım resim yaparak sürdürmektedir. Bedri Rahmi sanatı salt resim olarak değil, bir disiplinler bütünü olarak görür ve bir sanatçının da bu disiplinlerin her birinden haberdar olması gerektiğini düşünür. Bunu da yetiştirdiği tüm öğrencilerine aşılar. Bunu söylerken de kendi yaşamım ortaya koyar. Çünkü Bedri Rahmi hocalık kimliğinin dışmda kendisi de çok yönlü, sanatın bir çok dalma el atmış bir sanatçıdır. Resmin dışında kendi sanat hayatı boyunca baskılar yapmış; yazmalar basmış, duvar işçiliği yapmış; seramik ve mozaik tekniğini kullanmıştır. Bunların dışmda edebiyatçı kimliğiyle de kendini ortaya koymuştur. Yaşamı boyunca bir çok dergide yazı yazmış, günlük gazetelerde köşesi olmuş, şiirler yazmıştır. Bu edebiyatçı yönü kimi zaman ressam kimliğinin önüne geçmiş ve bir çok insan onu edebiyatçı, şair olarak tanımıştır. Yaptığı her işi de büyük bir ciddiyetle yapmış ve ciddiyetle ortaya koymuştur. Bunları yaparken de kendisi zaman içinde öğrendiği her yeni şeyi öğrencilerine de öğretmiştir. Bedri Rahmi gerek kişilik olarak, gerek sanat adamı olarak gerekse hoca olarak Akademi'nin diğer hocalarından çok farklıdır. En başta yansıttığı hava olarak diğerlerinden çok farklıdır, kılığı kıyafeti, konuşma tarzıyla hiçbir zaman klasik ve bürokrat görünüşlü bir hoca olmamıştır. Okul için de her zaman öğlencilerinin arkasında durmuş onları yeri geldiğinde savunabilmiştir. Kendi atölyesinde öğrencileriyle de alışılmışın dışında bir ilişki kurmuştur, öğrencileri ona karşı hem büyük bir saygı duyar, ondan çekinir hem de atölyenin kapısından çılanca bir arkadaş gibi yakın diyalog kurarlar. O da öğrencilerine çok bağlıdır. Hatta öyle ki öğrencilerinin büyük bir çoğunluğu son sınıfa gelip, okuldan mezun olsalar dahi Bedri Rahmi onlarla ilişkisini kesmemiştir.(Elbette resmi, sanatı hayatlarının içine almamış, hiç benimsememiş ve okuldan mezun olunca resim yapmayı hiç sürdürmemiş öğrenciler bu konunun dışmda kalıyorlar) Yaşamları boyunca onları bir şekilde takip etmiş ve resim yapmaları, sanatla ilişiklerini kesmemeleri açısından sürekli teşvik etmiştir. Bir atölye hocası olarak da öğrenciye hiç bir konuda baskı kurmamıştır, resim yapmayı basmakalıp bir teknik olarak görmemiş ve herkese aynı teknikle resim yapamayacaklarını öğretmiştir. Onun atölyede öğrenciye sunduğu resim eğitimi Vil yöntemi sadece bir anahtar işlevi görmektedir. Öğrenciyi asıl beslenme kaynağı olarak resim sanatı tarihine yönlendirmiştir. Yine bu atölyeye özgü bir durum da Bedri Rahmi'nin öğrencilerinden kendilerine birer usta seçmelerini istemesidir. Öğrenciler sanat tarihinin büyük ustalarına bakıp kendilerine birer usta seçeceklerdir. Böyle bir yönlendirme sonucunda da Bedri Rahmi atölyesinde yetişen her öğenci başka bir yola girecek ve bu şekilde atölye de basma kalıp değil birbirinden çok başka resimler çıkacaktır. Öğrencilerinin bakış açılarım genişletip, vizyonlarını açmak için bu çok etkili bir yöntem olmuştur. Bu yolla öğrenci sürekli araştırıp, incelemeye teşvik edilmektedir. Bedri Rahmi bu doğrultuda çok farklı yönlere ilgi gösteren öğrencüerinin kişisel eğilimlerine de çok saygı göstermektedir. Bedri Rahmi için öğrencide olması gereken en temel özellik çalışkan olmasıdır, yoksa nerede ve ne şekilde çalıştığının hiç önemi yoktur. Öğrenci hocaya haber vermek kaydıyla her gün atölyeye gelmeyebilir ama döndüğünde ona bu süre zarfında yaptığı çalışmaları gösterme zorunluluğu vardır. Bedri Rahmi'nin bu serbest eğitim politikası içinde nasıl ki resim tekniği, resim üslubu açısından bir zorlaması yoktu; malzeme olarak ta öğrenciyi tamamen serbest bırakmaktadır, öğrenci resmini ister boyayla yapar, ister kumla çalışır, isterse de tuvale bir başka malzeme yapıştırabilirdi. Bu noktada denebilir ki Bedri Rahmi döneminin ötesinde bir düşünce yapısına sahiptir. Bu konudaki serbestliği kendi sanatında da görmekteyiz, o da bir dönemden sonra kendi işlerinde çok değişik malzeme ve teknik arayışlarına girmiştir ve bunları uygulamıştır. Sanatçı kişiliğiyle de Bedri Rahmi sanatı yalnız üst düzey ve entellektüel bir kesimin görüp anlayacağı birşey olarak görmez. Kendi yaptığı eserlerini, çalışmalarım da özellikle halkın gözü önüne serer (mozaik ve seramik duvar panoları). İster ki onun işleri halkla içice girsin, onların yaşamlarının içine girsin, hatta bir kullanım aracı (yazmalar, seramik objeler) olarak yer alsın. Öğrencileriyle ilişkilerini sadece Akademi sınırları içerisinde tutmadan, onları kendi yaşamının her alanına sokmuştur. Onlarla Narmanlı Han'da beraber yazma basıp, dışarıda duvar panolarında birlikte çalışıp, yeri geldiğinde evinde rakı sofrasına da öğrencilerini konuk etmiştir. Bu nedenle Bedri Rahmi'nin öğrenci-öğretmen ilişkisi bugün bile alışılmış öğrenci-öğretmen ilişkisinden çok farklıdır, öğrencisine "resim nasıl yapıhr"ı değil, "nasıl ressam olunur, nasıl sanatçı olunur"un yollarını öğretmiştir. Ona göre; resim yapmak bir şekilde, her yerde, her zaman yapılabilecek bir iştir ama sanatçı olmak bir yaşam biçimi ve bir hayat görüşüdür. Kendi resim sanatında uzunca bir dönem etkin olan ve bazı öğrencüerinin de etkilendiği konu, yerellik ve halk sanatlarıdır. Bu özellikle Bedri Rahmi'nin ilk dönemlerinde üzerinde durduğu ve resimlerine de yansıyan bir konudur. Bazı öğrencileri bu konulan sıcak bulmuş ve yaklaşmış bazıları ise biç benimsememiştir. Ama bu şekilde öğrencilerine ulusal sanatla evrensel sanata gidilebileceğini öğretmiştir.

Teacher at a studio of the Istanbul State Fine Arts Academy between the years 1942- 1975, Bedri Rahmi Eyüboğlu's most important characteristic was his openness, while the most dominant characteristic of his studio was its unrestrictedness and freedom. More than just how to paint, he taught each of his students first and foremost how to become an artist and turn this into a lifestyle and philosophy of life by assuming the manners and attitudes of an artist throughout their lives. Most of the students he instructed in his studio adopted this way of understanding, which is why many of his students are still spending their lives painting. Bedri Rahmi did not view art merely as painting but rather as comprising all disciplines and so he believed that an artist must be well-informed about each of the disciplines. He instilled this belief in all of his students as well. Bedri Rahmi also puts these beliefs of his into practice in his own life as an artist who, in addition to being a teacher, was an artist of many abilities who tried his hand at many different branches of art. In addition to painting, he also made prints throughout his artistic life; he made prints on hand-painted cloth and worked on wall construction and decoration and also used ceramic and mosaic techniques. Moreover, he also became known as a literary figure. He wrote for many magazines, had a column in daily newspapers and composed poetry throughout his life. His identity as a man of letters sometimes overrode his identity as an artist and so many people came to know him as writer of literature and poetry. Everything he did, he did with great earnestness, and he presented the products of his efforts with great earnestness as well. While carrying out all of his work, he also taught his students everything he had learned over time. In terms of personality as well as his identity as a man of arts and a teacher, Bedri Rahmi was different from the Academy's other teachers. First of all, he was different from the others in terms of his style; with his manner of dressing and speaking, he was never a teacher of classical and bureaucratic appearance. At school he always stood behind his students and defended them when necessary. He established a relationship with his students in his own studio that was truly out of the ordinary; his students held him in great esteem while at the same time they felt shy in front of him. Nevertheless, outsiside of the studio, his students could establish a close dialogue with him as between friends. He himself was also very attached to his students. So much so that, even after they had become seniors and then graduated, Bedri Rahmi did not end his relations with the majority of his students. (Of course, those students who did not include painting in their artistic lives and did not make painting a part of their lives and therefore did not continue painting whatsoever after graduating were not among those.) One way or the other, he kept abreast of what they were up to throughout their lives and encouraged them not to end their relationship with art. IX As a studio teacher he did not put any pressure on his students, did not view painting as an act of merely conventional techniques and taught that not everyone was going to be able to paint using the same techniques. The method of painting education that he gave his students in the studio functioned as a key. He directed his students to the history of painting as the source from which they should nourish their own art. Another situation that was unique to this studio was Bedri Rahmi' s request that each of his students choose a master for him- or herself The students were to look back to a great master in the history of art and choose one for themselves. As a result, every student educated in the studio of Bedri Rahmi would take a different path, hence what emerged from the studio were not stereotypical paintings but rather paintings that were very different from one another. This was an extremely effective method for expanding the students' perspectives and getting them to project their own visions. In this way, students were encouraged to constantly research and analyze. In this regard, Bedri Rahmi also showed great respected the tendencies of those students who exhibited interest in very different points of view. For Bedri Rahmi, the most fundamental characteristic that his students had to possess was industriousness; without this characteristic, it did not matter where or how s/he worked. A student did not have to come to the studio every day so long as s/he told the teacher ahead of time; however, when s/he did show up after an absence, s/he had to show the teacher what s/he had done during the time of absence. In accordance with Bedri Rahmi' s politics of an open style of education, just as there was no pressure on the students with regard to painting technique or style, so too were his students completely free to use whatever materials they chose to use. If s/he wanted, a student could use paint or work with sand or apply any other material to the canvas. In this respect also it can rightly be said that Bedri Rahmi' s thinking was well beyond his time. We see his openness in this regard in his own art as well; in his quest for different materials and techniques, experimented with a wide variety of materials and techniques which he applied to his own work as well. As an artist, Bedri Rahmi did not view art as something that only an elite and intellectual segment of society could see and understand. He exhibited his own work before the people (mosaic and ceramic wall panels). He wanted his work to be accessible to the people and for them to be able to relate to it, for it to become a part of their lives and even take its place in their lives as a functional means they could use (cloth with prints, ceramic objects). He did not limit his relations with his students to the Academy but included them in every aspect of his life. He made prints on cloth with them at Narmanli Han, worked together with them on wall panels outside and even invited them to his house for dinner and drinks when appropriate. It is for this reason that Bedri Rahmi's student- teacher relations were very different from ordinary student-teacher relations even today. He taught his students not "how to paint", but rather showed them "how one becomes a painter, how one becomes an artist". In his eyes, painting was something that could be done anywhere at any time whereas being an artist was a lifestyle and way of viewing life. A topic that was influential in his own artistic life for a long period of time and that also influenced some of his students was that of localness and folk art. This is a topic that Bedri Rahmi emphasized in his earliest periods and that was reflected in his paintings. While some of his students did not incorporate this into their work at all, others found this topic ineresting and worked with it themselves. It was through this topic of localness and folk art that Bedri Rahmi taught his students that one could produce universal art by way of national art.
Bedri Rahmi Eyüboğlu As Educator
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2003
Thesis (M.A.) -- İstanbul Technical University, Institute of Social Sciences, 2003
Keywords: Biyografi; Sanat Tarihi; Bedri Rahmi Eyüboğlu; Eğitimciler; Ressamlar; Sanat eğitimi; Sanatsal yaşam; Sanatçılar; Biography; Art History; Bedri Rahmi Eyüboğlu; Educators; Painters; Art education; Artistic life; Artists